Analisis Fraksi Volume Bahan Bakar Uranium Karbida Pada Reaktor Cepat Berpendingin Gas Menggunakan SRAC Code - Ratna Dewi Syarifah; Nabil Nabhan MH; Zein Hanifah; Iklimatul Karomah; Ahmad Muzaki Mabruri; Artoto Arkundato (Jurnal Jaring SainTek, 2021)
Analysis of fuel volume fraction with uranium caride fuel in Gas Cooled Fast Reactor (GFR) with SRAC Code is has been done. The calculation used SRAC Code (Standard Reactor Analysis Code) which is developed by JAEA (Japan Atomic Energy Agency), and the data libraries nuclear used JENDL 4.0. There are two calculation has been used, fuel pin cell calculation (PIJ Calculation) and core calculation (CITATION Calculation). In core calculation, the leakage is calculated so the calculation more precise. The CITATION calculation use two type of core configuration, i.e. homogeneous core configuration and heterogeneous core configuration. The power density value of two type core configuration is quite difference. It is better use heterogeneous core configuration than homogeneous core configuration, because the power density of heterogeneous core configuration is flatter than the other. From the analysis of fuel volume fraction, when the volume fraction is increase, the k-eff value is increase. And the optimum design after has been analysis for fuel volume fraction, that is the fuel volume fraction is 49% with a heterogeneous core configuration of three types of fuel percentages, for Fuel1 9%, Fuel2 12% and Fuel3 15%. This reactor is cylindrical, has a core diameter of 240 cm and a core height of 100 cm.